2003
DOI: 10.1074/jbc.m211622200
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Epsin Ent1 Is Recruited to Membranes through Multiple Independent Interactions

Abstract: In addition to its well known role in targeting proteins for proteasomal degradation, ubiquitin (Ub) is also involved in promoting internalization of cell surface proteins into the endocytic pathway. Moreover, putative Ub interaction motifs (UIMs) as well as Ub-associated (UBA) domains have been identified in key yeast endocytic proteins (the epsins Ent1 and Ent2, and the Eps15 homolog Ede1). In this study, we characterized the interaction of Ub with the Ede1 UBA domain and with the UIMs of Ent1. Our data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
128
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 27 publications
4
128
0
Order By: Relevance
“…The ability of Cbl-b to bind to ubiquitinated proteins via its UBA domain is similar to a number of other UBA domain containing proteins (Chen and Madura, 2002;Funakoshi et al, 2002;Meyer et al, 2002;Aguilar et al, 2003;Ryu et al, 2003). Since the UBA b binds free ubiquitin in vitro, it is likely that the association of Cbl-b with ubiquitinated proteins is due to the binding of ubiquitin conjugated to these proteins.…”
Section: Discussionmentioning
confidence: 86%
“…The ability of Cbl-b to bind to ubiquitinated proteins via its UBA domain is similar to a number of other UBA domain containing proteins (Chen and Madura, 2002;Funakoshi et al, 2002;Meyer et al, 2002;Aguilar et al, 2003;Ryu et al, 2003). Since the UBA b binds free ubiquitin in vitro, it is likely that the association of Cbl-b with ubiquitinated proteins is due to the binding of ubiquitin conjugated to these proteins.…”
Section: Discussionmentioning
confidence: 86%
“…The function of these UIMs is to bind ubiquitinated cargo Shih et al, 2002;Aguilar et al, 2003). Ent3p and Ent5p are required for ubiquitin-dependent sorting at the MVB, but they do not possess obvious ubiquitin-binding domains (UBC-like, UIM, UBA, or CUE; Hofmann and Bucher, 1996;Hofmann and Falquet, 2001;Polo et al, 2002;Shih et al, 2002).…”
Section: Ent3p and Ent5p Do Not Directly Bind To Ubiquitinmentioning
confidence: 99%
“…For binding to ubiquitin-sepharose, 50 l ubiquitin-sepharose (Sigma) was incubated with 20 g recombinant protein for 4 h, and washed in TBST as described (Aguilar et al, 2003).…”
Section: Pull-down Experiments and Ubiquitin-binding Assaysmentioning
confidence: 99%
“…UIMs of epsins and Eps15 bind directly to ubiquitin (Polo et al, 2002;Shih et al, 2002;Aguilar et al, 2003). In yeast, it was recently demonstrated that Ent1, Ent2, and Ede1 (the homologues of human epsins 1 and 2 and Eps15, respectively) have redundant functions in internalization of the pheromone receptor Ste2 (Shih et al, 2002).…”
Section: Introductionmentioning
confidence: 99%